Didactic Guide: Environmental Education against Climate Change and its Effects on Biodiversity (Biocenosis, 2021)
The phenomenon of climate change, together with global change, overexploitation, pollution, and the introduction of exotic species, is considered one of the main agents that cause the decrease and disappearance of many flora and fauna species worldwide.Because of this global phenomenon, currently and in the future, many negative effects on flora and fauna are expected, so it is urgent to implement actions from communities and educational centers that enable their conservation. The guide seeks to be a tool so that environmental educators can continue to deliver a message that facilitates sensitizing the general population, in order to implement local activities and actions that affect the national, regional and global levels.
Keywords: climate change; impact; biodiversity; society; community